Tirpitz the life and death of Germany's last super battleship - Zetterling, Niklas 1963-; Tamelander, Michael 1960- (Casemate, 2009)
The final days of Germany's greatest battleship illuminates the strategic implications and dramatic battles surrounding the "Tirpitz," a ship that may have had greater influence on the course of World War II than her more famous sister, the "Bismarck."